Challenges of Becoming a Scholar: A Study of Doctoral Students' Problems and Well-Being. (16th October 2012) - Pyhältö, Kirsi; Toom, Auli; Stubb, Jenni; Lonka, Kirsti
Abstract : Successful studying in Ph. D. education is a complex matter. Although Ph. D. students are a highly select group, some never finish. This paper explores the problems that doctoral candidates face during their doctoral studies as well as students' well-being in relation to their studying engagement. The study is part of a larger research project on doctoral education. Altogether 669 doctoral students from the Faculties of Arts, Medicine, and Behavioural Sciences responded to the survey. Doctoral students' perceptions of the problems they encountered during their studies varied. The problems reported were related to general working processes, domain-specific expertise, supervision, the scholarly community, and resources. Doctoral students' well-being and study engagement showed a clear relationship. More effective means are needed to foster students' ability to overcome problems encountered during their Ph. D. studies.